Awareness of students on drug addiction its relationship to their health values: basis for drug abuse preventive intervention - Benjamin, Marian J. (Manila : National University, 2013)
The researcher opted to use her work place as the venue of the study. The extent of the awareness and health values of the third year students in drug abuse will be assessed.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.